PENGARUH NON PERFORMING LOAN DAN GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN DI SEKTOR PERBANKAN - Asep Asep Saeful Falah; Tantri Wijaya (JURNAL EKONOMI PERJUANGAN, 2026)
This study investigates the impact of Non-Performing Loans (NPL) and Good Corporate Governance (GCG) on firm value in banking companies listed on the Indonesia Stock Exchange (IDX) during the 2012–2022 period. The sample was selected using a purposive sampling technique, resulting in three banks that met the research criteria, with a total of 33 observations. The data were analyzed using multiple linear regression with the assistance of SPSS version 26. The findings reveal that Bank Central Asia (BBCA) recorded the lowest NPL ratio among the sampled banks, indicating a relatively better level of credit quality. Meanwhile, Bank Mandiri (BMRI) achieved the highest GCG score, reflecting stronger corporate governance practices. In terms of firm value, measured by the Price-to-Book Value (PBV) ratio, BBCA outperformed the other banks by attaining the highest PBV level. The partial regression results demonstrate that NPL has a significant negative effect on firm value, suggesting that an increase in problematic loans tends to reduce a bank’s market valuation. Conversely, GCG exerts a significant positive influence on PBV, implying that effective governance mechanisms can enhance stakeholder confidence and contribute to higher firm value. Furthermore, the simultaneous test indicates that NPL and GCG jointly have a significant effect on firm value. The model's explanatory power is reflected in an Adjusted R-squared value of 73.8%, meaning that variations in firm value can be explained by NPL and GCG, while the remaining 26.2% is attributable to other factors not included in the research model.